1976
DOI: 10.1152/ajplegacy.1976.230.4.916
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal villus blood flow measured with carbon monoxide and microspheres

Abstract: The purpose of the present study was to compare the small intestinal blood flow that equilibrates with luminal CO (FLco) with simultaneous determinations of villus blood flow measured by a recent modification of the microsphere technique. These studies, carried out in rabbits, showed that FLco closely correlated (r = 0.83) with villus flow measured with microspheres over a three-fold range of flows, and the mean rate of flow to the villi by both techniques was about 0.08 ml/min X g of intestine. Thus, FLco app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Thus, the SFM recognizes the subtle demarcation of tissue layers and distributions in blood supply (Svanvik, 1973;Granger et al, 1980). The literature values for the blood flow to the absorptive enterocyte layer of the mucosa vary greatly, ranging from 5% to 30% (Micflikier et al, 1976;MacFerran and Mailman, 1977;Mailman 1978;Granger et al, 1980). Drug in the lumen must enter via the enterocyte region before reaching the circulation, whereas drug already in circulation is primarily channeled to other tissular regions.…”
Section: Fig 6 Simulations Based On Intestinal Modeling For the Ratmentioning
confidence: 99%
“…Thus, the SFM recognizes the subtle demarcation of tissue layers and distributions in blood supply (Svanvik, 1973;Granger et al, 1980). The literature values for the blood flow to the absorptive enterocyte layer of the mucosa vary greatly, ranging from 5% to 30% (Micflikier et al, 1976;MacFerran and Mailman, 1977;Mailman 1978;Granger et al, 1980). Drug in the lumen must enter via the enterocyte region before reaching the circulation, whereas drug already in circulation is primarily channeled to other tissular regions.…”
Section: Fig 6 Simulations Based On Intestinal Modeling For the Ratmentioning
confidence: 99%
“…Thus, CO-uptake from the canine bladder (Cobum et al 1968) and from the rabbit ileum (Coburn 1968) seemed to be blood flow limited when PCO in the lumen exceeded 50 kPa. Furthermore, Micflikier et al (1976) found a good correlation between villous blood flow in the rabbit small intestine measured with microspheres and with carbon mon- oxide. However, in the canine small intestine COuptake remained diffusion limited even when pure CO was installed into the intestinal lumen .…”
mentioning
confidence: 78%
“…This technique allows, however, only a limited number of observations in each experiment. A few attempts have been made to study villous blood flow separately using microspheres (Bond et al , 1980 or an indicator dilution method (Svanvik 1973) or by measuring the rate of CO absorption (Coburn 1968, Bond et al 1974, Micflikier et al 1976.…”
mentioning
confidence: 99%
“…Grim and Lindseth [1958], using glass microspheres with diameters of 12 ± 1.2 Mm, observed an arteriovenous shunting of 17-28% in the small bowels of dogs. Micfukier et al [1976] found that 16% of 7-to 10 ,t/m carbonized micropheres were shunted across the intestines of rab bits. In the present experiment, where blood flow distribution in the small bowels of cats was estimated, it would be desirable to determine the arte riovenous shunting in each different layer of the intestinal wall.…”
Section: Discussionmentioning
confidence: 99%